COMUNICACIÓN DESTRUCTIVA Y NUEVA BARBARIE EN WALTER BENJAMIN - Pignuoli Ocampo, Sergio (Caderno CRH, 2020)
En este trabajo se indagan los elementos conceptuales con que Walter Benjamin reflexionó sobre la comunicación tras su giro hacia el materialismo histórico a mediados de la década del veinte. Sobre esa base se desarrolla un sistema de categorías sobre la comunicación en conexión con dichos elementos y se hace especial hincapié en el concepto de comunicación destructiva. La hipótesis del trabajo es que el concepto de comunicación destructiva unificó la intervención de Benjamin en aquel momento histórico y constituyó el reverso del concepto positivo de barbarie. DESTRUCTIVE COMMUNICATION AND NEW BARBARISM IN WALTER BENJAMIN This paper explores the conceptual elements with which Walter Benjamin reflected on communication after his shift towards historical materialism in the mid-1920s. On this basis is a category system developed for communication in connection with these elements, with particular emphasis on the concept of destructive communication. The hypothesis of the paper is that the concept of destructive communication unified Benjamin’s intervention at that historical moment and constituted the reverse of the positive concept of barbarism. Keywords: Historical Materialism. Communication Theory. Modernity. Russian Constructivism. COMMUNICATION DESTRUCTRICE ET NOUVELLE BARBARIE CHEZ WALTER BENJAMIN Cet article explore les éléments conceptuels avec lesquels Walter Benjamin a réfléchi sur la communication après son passage au matérialisme historique au milieu des années 20. Sur cette base, un système de catégories sur la communication en rapport avec ces éléments est développé et un accent particulier est mis sur le concept de communication destructive. L’hypothèse de l’œuvre est que le concept de communication destructive a unifié l’intervention de Benjamin à ce moment historique et a constitué l’inverse du concept positif de barbarie. Mots-clés: Matérialisme historique. Théorie de la communication. Modernité. Constructivisme russe.